2018
DOI: 10.1002/ijch.201700081
|View full text |Cite
|
Sign up to set email alerts
|

[1, 2]‐Migration Reactions Catalyzed by Gold Complexes and their Applications in Total Synthesis

Abstract: The area of cascade reactions, initiated by the transition metal‐catalyzed activation of π‐systems and coupled with a 1,2‐migration step is of considerable interest in current organic chemistry research. In this article, recent advances in the field are highlighted, focusing on gold as the activating π‐acid. Cascade reactions with 1,2‐shifts of alkyl groups as migrating agents are mainly presented, but also selected 1,2‐aryl migrations and miscellaneous examples are depicted. With the reactions discussed, mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 113 publications
0
8
0
Order By: Relevance
“…With 5a as a representative example, this may initially involve activation of the propargyl moiety of the substrate by the Au I catalyst to give the gold(I)-coordinated complex IIIa. This results in the [2,3]-sigmatropic rearrangement of the acetyl functional group to produce the gold carbenoid species Va via the 1,3dioxin-1-ium intermediate IVa. Trapping of this newly formed organogold species by the remaining alkyne motif may then provide the putative cyclopropene adduct VIa.…”
Section: Resultsmentioning
confidence: 99%
“…With 5a as a representative example, this may initially involve activation of the propargyl moiety of the substrate by the Au I catalyst to give the gold(I)-coordinated complex IIIa. This results in the [2,3]-sigmatropic rearrangement of the acetyl functional group to produce the gold carbenoid species Va via the 1,3dioxin-1-ium intermediate IVa. Trapping of this newly formed organogold species by the remaining alkyne motif may then provide the putative cyclopropene adduct VIa.…”
Section: Resultsmentioning
confidence: 99%
“…In 1987, the first homogeneous gold-catalyzed addition of nucleophiles to alkynes was realized by the group of Utimoto using sodium tetrachloroaurate dihydrate. , One decade later, Teles et al and Tanaka et al demonstrated the possibility of activating alkynes using gold­(I) complexes. From that point, the field of gold­(I) catalysis started to gain momentum year after year and still today remains one of the most active areas of research in organometallic chemistry. , This comes as a consequence of the ability of gold­(I) complexes to activate π bonds in a very selective manner. Its potential, attributed partially to relativistic effects, is illustrated by the wide molecular complexity that can be built through the gold­(I)-catalyzed cycloisomerization of enynes (Scheme ). …”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Hashmi described an efficient method for the preparation of 3-formylfurans by a gold­(I)-catalyzed oxidation/1,2-alkynyl migration/cyclization cascade (Scheme d) . However, the incorporation of a 1,2-migration of an alkyl or aryl group in a gold-catalyzed cascade reaction for the synthesis of novel complex polycyclic scaffolds is rare . Recently, we developed a gold-catalyzed annulation of Ugi adducts for the preparation of structurally complex polyheterocycles via a cascade nucleophilic cyclization/intramolecular 1,3-migration/1,5-enyne cycloisomerization process (Scheme e) .…”
mentioning
confidence: 99%